2020
DOI: 10.1155/2020/9631851
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Characteristics of Cardiovascular Changes in Children with Hutchinson–Gilford Progeria Syndrome: A Comparative Study with Normal Children and Aging People

Abstract: Background. The cardiovascular characteristics of children with Hutchinson-Gilford progeria syndrome (HGPS) remain unclear. The present study is aimed at evaluating the cardiovascular changes with ultrasound examination in children with HGPS and compared these with those in normal children and older people. Methods. Seven HGPS children, 21 age-matched healthy children, and 14 older healthy volunteers were evaluated by three-dimensional echocardiography (including strain analysis) and carotid elasticity examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Degenerative cardiac findings differ from the natural ageing process, with highly accelerated calcium deposition in the coronary arteries, aortic artery, aortic and mitral valve cusps, and mitral annulus. 5 There were few therapeutical options; recently, new medical treatments and percutaneous interventions have brought some hope for progeria patients.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative cardiac findings differ from the natural ageing process, with highly accelerated calcium deposition in the coronary arteries, aortic artery, aortic and mitral valve cusps, and mitral annulus. 5 There were few therapeutical options; recently, new medical treatments and percutaneous interventions have brought some hope for progeria patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increased echobrightness was not associated with age, suggesting that extracellular matrix (ECM) remodeling may be an early alteration potentially underlying the development of the cardiac phenotype. Another recent study [ 37 ] applied three-dimensional echocardiography (speckled tracking imaging) to analyze seven HGPS patients (five children ≤ 8 years of age and two children in their teens), 21 aged-matched healthy children, and 14 older healthy volunteers (mean age: 65.7 ± 7.5). Despite the fact that most HGPS patients were in their first decade of life, the authors found one case of diastolic dysfunction and another of aortic valve calcification, severe aortic stenosis, and LV hypertrophy, in agreement with some of the findings reported by Prakash et al [ 30 ].…”
Section: The Cardiovascular Phenotype In Hgps Patients: a Historical Perspectivementioning
confidence: 99%